Native Species in Barito Upstream at South Kalimantan, Indonesia: Sex Ratio and Length-Weight Relationship of Seluang Batang Fish (Rasbora argyrotaenia Blkr 1850) - Erwin Rosadi; Endang Yuli H.; Daduk Satyohadi; Gatut Bintoro (Journal of Wetlands Environmental Management, 2016)
Freshwater potential in South Kalimantan is one million hectares and 140 species of fish are exploited. One of the fish resources in the intensive exploitation in South Kalimantan is Seluang Batang fish (Rasbora argyrotaenia). The purpose of this study was to obtain scientific data related to the sex ratio of fish and length-weight relationships of R. argyrotaenia in Barito upstream at South Kalimantan. The study was conducted in the Barito upstream in South Kalimantan, on location 2o57'36.10'' S 114o5'37.92'' E; 3o01'07.86" S 114o45'29.28'' E. Taking of samples by the method of Ford-Walford plot lasts for one year with a fixed time interval decision which is one month. Data obtained by comparing the sex ratio between the number of male fish with the number of females and multiplied by 100%. To test the hypothesis difference in the number of male and female fish used chi-square analysis of the end. Analysis of length-weight relationship of fish with regression test and were calculated using a cubic pattern. The results showed that the ratio of fish R. argyrotaenia male and female is 3: 1 and the growth pattern of male and female fish are negative allometric.